EDUCATION RELATED TO THE EFFECT OF TRUNK MUSCLE EXERCISE ON REDUCING THE RISK OF FALLING IN THE ELDERLY: EDUCATION RELATED TO THE EFFECT OF TRUNK MUSCLE EXERCISE ON REDUCING THE RISK OF FALLING IN THE ELDERLY - Bintang, Siti Sarah; Siahaan, Timbul; Br Tambunan, Juni Kristina; Harahap, Fitri Ramadhani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Decreased physical function and a significant increase in the risk of disability and dependency are typical of older adults. Muscle strength is a strong predictor of severe mobility limitations, slow walking speed, increased risk of falls. Research provides justification for the use of trunk muscle exercise therapy which plays a restorative and accommodative role in minimizing loss of stability in the elderly through improving balance and mobility thereby reducing the risk of falls. This community service activity (PKM) uses a lecture technique by providing education about Education Related to the Effect of Trunk Muscle Exercise on Reducing the Risk of Falling in the Elderly. The media used in the lecture technique. Implementation of PkM activities for the elderly, carried out through notifications via the internet by filling out a Google form with a sample size of 12 elderly. The results obtained are increased knowledge related to education related to the effect of trunk muscle training on reducing the risk of falling in the elderly